Mathematical meaning construction in language, tables, and images: The potential utility of language proficiency development in numeracy teaching - Clarke, Jumani (Critical Studies in Teaching and Learning, 2024)
Numeracy entails a facility for communicating mathematical knowledge in diverse contexts. Indeed, large scale standardised assessments have demonstrated that numeracy is associated with both mathematics and language proficiency. And yet, while research in mathematics education in schools has demonstrated the utility of taking a discursive view of mathematics, similar developments in higher education studies are scarce. Moreover, as teaching interventions in numeracy may lead to tensions between mathematical and disciplinary knowledge, the prospect of including language proficiency development is challenging. Taking a discursive multimodal view, this study reports on a pilot teaching intervention that introduced explicit language proficiency development into numeracy teaching activities at a prominent South African university. The study found that the participants produced coherent descriptions of statistics when mathematical concepts were related to vocabulary and grammar. These observations suggest that language proficiency development has the potential to realise the goal of teaching mathematical knowledge within disciplinary curricula.